Threshold π0 photoproduction on transverse polarised protons at MAMI; Physics Letters B; Vol. 750 - Schumann S.; Otte P. B.; Akondi C. S.; Annand J. R. M.; Arends H. J.; Beck R.; Bernstein A. M.; Borisov N.; Braghieri A.; Briscoe W. J.; Cherepnya S.; Collicott C.; et al. (2015, 2015)
Title screen